Beethoven monument in Bonn - Strunz, C. (engraver):::Creator::::::::::::; Schallenberg, J.C. (photographer):::Contributor::::::::::::; Hähnel, Ernst Julius, 1811-1891 (sculptor):::Contributor:::::::::::: (Germany; C. Koehler jr.; Darmstadt)
Engraving of sculptor Ernst Julius Hähnel's Beethoven monument in Bonn based on a photograph by J. G. Schallenberg.